Critical Analysis of Etiopathology of Cervical Lymphadenopathy in patients reporting to the Department of Surgery Chandka Medical College Hospital Larkana - Nargis Shaikh, Aisha Shaikh, Saira Fatima, Ibrahim Asghar, Kanwal Qureshi (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Nodes that are aberrant in their size, consistency, or number are referred to as lymphadenopathy. Study Duration: Current research was carried out at Surgery Department of Chandka Medical College (CMC) & Teaching Hospital, Larkana starting from March 2019 to September 2020. Subjects & Methods: After taking written informed consent, 162 patients was included in the study after fulfilling of the inclusion criteria. Chi square test was applied and P-value <0.05 was considered significant Results: The results of reactive/benign in our study were as out of 162 patients 54(33.3%) belongs to positive group and 108(66.7%) belongs to negative group. In tuberculous the frequency distribution results showed that 57(35.2%) positive and 105(64.8%) were negative. In causing factors the results of malignant frequency distribution were as out of 162 patients 51(31.5%) were positive and 111(68.5%) were negative. Conclusion: In conclusion, our study reveals a lower prevalence of malignancy, reactivity, and benign causes of cervical lymphadenopathy, and an increased prevalence of Tuberculosis as a cause of cervical lymphadenopathy in patients presenting to the surgery department at CMC Hospital in Larkana. To avoid lengthy delays in identification and treatment of numerous medical diseases, including potentially curable malignancies, we advocate for conducting biopsy early in the workup of cervical lymphadenopathy. Keywords: Cervical lymphadenopathy, lymphoma, Tuberculous. Etiopathology, Chandka Medical College